5-Years Prevalence Study of HBV and HCV infections in Babylon Province: Forensic Helping Data - Kadhim Jawad Mohammed1 , Hussein O.M. Al-Dahmoshi2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
HBV and HCV infections are serious global health care problem because they may end with chronichepatitis, cirrhosis, and hepatocellular carcinoma. HBV infection results in approximately 2 billion humaninfections while HCV approximately 160 million individuals. Raw database were collected from Generalhealth department at Babylon Health directorate for 715505 investigated person during a period from Jan.2015 to Dec. 2019. Blood samples was drawn in Gel tube from suspects and centrifuged to separate theserum. Serum submitted for investigation of HbsAg and HCV Ab by both rapid immunochromatographictest and ELISA test. Actually the database taken from Babylon Health directorate and the results analysisdepends upon dividing of data records from four health sectors, blood bank record lab, health care checkinglab, pre-surgery checking, Marriage lab, thalassemia lab, Hemodialysis lab Prisoner and foreigners lab. Theresults revealed that , total positive cases were 4284 and 2260 for “HBV and HCV” respectively. The highestno. of cases for both “HBV and HCV” were recorded in 2018 (976 and 467) and (961 and 557) for “HBVand HCV” respectively. The incidence rate of “HBV and HCV” were varies worldwide. The results revealedthat the occurrence rate (Mean ± SD) of “HBV” was (0.627±0.134) while for HCV was (0.327±0.084). Theresults revealed that, there is no defined month or semester for high rate infections. The high prevalencepercentage were showed for prisoner-foreigner category (48.53 and 45.95 for HBV and HCV respectively)followed by surgery (22.66 and 19.03 for HBV and HCV respectively), blood bank (14.03 and 13.95 forHBV and HCV respectively) and in married (7.79 and 3.92 for HBV and HCV respectively. The current studyconclude the high prevalence percentage of HBV (duplicate) than HCV with no seasonality of occurrenceand the Prisoners and foreigners, Surgery, blood donor and hemodialysis were mostly involved with HBVand HCV infection.